The Effectiveness of Psychoeducational Group with Group Exercises Technique to Improve Student’s Self-Efficacy - Pangestuti, Riana Wibi; Wibowo, Mungin Eddy; Japar, Muhammad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
Self-efficacy is a determining factor to achieve the learning objectives. Therefore, self-efficacy is important to be measured and improved. This study aimed to examine the effectiveness of a psychoeducational group with exercises techniques to improve students’ self-efficacy. This study was carried out by using a pretest-posttest control group design by involving 2 groups, the experimental and control group. The data from these groups were analyzed using repeated-measure MIX MANOVA. Meanwhile, the authors used self-efficacy scale (α=0.911) to collect the data of 14 students. The results showed that there were effects of time in the improvement of students' self-efficacy (F(2)=1,746; p<0.05), group members effect (F(3,984)=8,442; p<0.05), and the effect of time interacting with group members (F(1,293)=0.045; p<0.05). It can be concluded that the psychoeducational group with exercises techniques is effective to improve students’ self-efficacy by regarding the duration of intervention, group member, and time interaction with group members. This study implication to the guidance and counseling services will be discussed.